Structural and surface functionality changes in reticulated vitreous carbon produced from poly(furfuryl alcohol) with sodium hydroxide additions - Oishi, Silvia Sizuka; Botelho, Edson Cocchieri [UNESP]; Rezende, Mirabel Cerqueira; Ferreira, Neidenêi Gomes (Elsevier, 2017)
The use of sodium hydroxide to neutralize the acid catalyst increases the storage life of poly(furfuryl alcohol) (PFA) resin avoiding its continuous polymerization. In this work, a concentrated sodium hydroxide solution (NaOH) was added directly to the PFA resin in order to minimize the production of wastes generated when PFA is washed with diluted basic solution. Thus, different amounts of this concentrated basic solution were added to the resin up to reaching pH values of around 3, 5, 7, and 9. From these four types of modified PFA two sample sets of reticulated vitreous carbon (RVC) were processed and heat treated at two different temperatures (1000 and 1700 °C). A correlation among cross-link density of PFA and RVC morphology, structural ordering and surface functionalities was systematically studied using Fourier transform infrared spectroscopy, scanning electron microscopy, Raman spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy techniques. The PFA neutralization (pH 7) led to its higher polymerization degree, promoting a crystallinity decrease on RVC treated at 1000 °C as well as its highest percentages of carboxylic groups on surface. A NaOH excess (pH 9) substantially increased the RVC oxygen content, but its crystallinity remained similar to those for samples from pH 3 and 5 treated at 1000 °C, probably due to the reduced presence of carboxylic group and the lower polymerization degree of its cured resin. Samples with pH 3 and 5 heat treated at 1000 and 1700 °C can be considered the most ordered which indicated that small quantities of NaOH may be advantageous to minimize continuous polymerization of PFA resin increasing its storage life and improving RVC microstructure.
Keywords: Microstructure; NaOH oxidation; Poly(furfuryl alcohol); Reticulated vitreous carbon; Surface functionalities